Essential oils and morphological study of Mentha aquatica - Chaker, Adel Nadjib; Boukhebti, Habiba; Sahraoui, Rachid; Ramdhani, Messaoud (Pharmacognosy Communications)
As part of the development of plant resources, we are interested in the chemical study of essential oils of Mentha aquatica that is widely used in Algerian traditional medicine. Essential oil extracted from this plant was obtained by hydrodistillation with a Clevenger type apparatus for a period of three hours. The extraction produced yellowish essential oils with a very strong odor. Chemical analysis of the essential oils was achieved by gas chromatography coupled with mass spectrometry (GC/MS). The major compound present in the essential oil of M. aquatica was found to be linalyl acetate (26.1 %), other constituents included α-Pinene (22.7 %), Linalol (13.8 %). The morphological study of M. aquatica shows two different types of glandular trichomes on both leaves and stems but lacunar parenchyma is only present in stem section.
Keywords: Essential oils; Chemical analysis; M. aquatica; (water mint); Morphological study